Social policy reforms and economic distances in China, 2002-2013 - Qin Gao; Sui Yang; Fuhua Zhai; Yake Wang (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2017)
Using the data from the China Household Income Project (CHIP) in 2002, 2007, and 2013, this chapter examines the effects of a series of social policy reforms on the economic distance between the rich and poor in each of the urban, rural, and migrant household sectors. We find that over the years pensions in the urban areas consistently helped narrow the economic distance among urban households, whereas other social benefits - including health insurance, social assistance, supplementary income, and in-kind benefits - had little or no redistributive impact. Both rural and migrant social benefits changed from being regressive in 2002 to becoming progressive in 2013. Among all social benefits in the rural areas in 2013, supplementary income and in-kind benefits in the form of agricultural and livelihood subsidies played the most significant redistributive role, while private transfers also helped to substantially narrow economic distances. Among migrants, in 2013 health benefits and taxes and fees helped narrow economic distances, although to a lesser extent as compared to the rural social benefits. Despite the expansion of social policy during this period, in both urban and rural China market forces still played a dominant role in widening the economic distance between the rich and poor, which trumped the redistributive effects of the social benefits. These results suggest that China's future social policy reforms face continued challenges in terms of unifying the urban-rural-migrant imbalances and keeping pace with the disequalizing market forces.
Keywords: H23; H55; O23; P35; 330; China; social policy; economic distance; inequality; pensions; agricultural subsidies